Technical analysis of men's singles final in the 2017 World Table Tennis Championships - Sung, C.-Y. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
This study was based on the men's singles champion Ma Long, who won the 2017 World Table Tennis Championships, and his final opponent, Fan Zhendong. Video recording was used to analyse and compare various technical performances of their competition. By doing the statistical analysis and discussion, the following conclusions were drawn: (1) The three-staged techniques scoring for Ma Long were: `attack after serve` and `rally` were rated "excellent", whereas `attack after receive` was rated "fail". His technical characteristics were fast in movement, fast paced game, and powerful serve. In addition, usually he was able to score critical point. While playing, often he could make critical attacks and endure long rally with positive attitude to win the point. Although he rarely returned the ball using `attack after receive` technique, he could effectively position the landing point of the ball when receiving the serve. Therefore, he was able to win the 2017 World Table Tennis Championships in Men`s singles. (2) Fan Zhendong`s three-staged techniques performance was solid, but it did not score as well as Ma Long`s. Overall, he got "excellent" in `attack after receive`, but was rated "fail" in both `attack after serve` and `rally`.